Women and The Poverty Trap (Study on The South Merapi Slope) - Hastuti Hastuti; Sri Agustin Sutrisnowati (Department of Geography Education, University of Jember, 2023)
The infection rate of COVID-19 has forced many households into economic hardship when poverty strikes, women are the most affected. In rural areas, the beginning of the poverty trap is economic difficulties in addition to reduced arable land. The research was conducted in Girikerto Kapanewon Turi District, women in the research areas experience increasingly complicated poverty traps. This study aims to find out the social conditions and economic conditions of women during COVID-19, the second objective is to find out the efforts made by women to escape from household poverty during the COVID-19 pandemic, and third to find out how women find alternative social and economic activities during COVID-19. To examine primary and secondary data related to demographics, descriptive quantitative data analysis is essential. Frequency tables are utilized to describe the distribution and pattern of features of particular variables. The demographic characteristics of women in the research region are dominated by their productive age, high school/vocational education, their status as housewives, and their employment in agriculture. The result show women can still meet their food needs from their limited agricultural land. The poverty trap experienced by women is the difficulty in fulfilling household needs other than food such as the cost of educating children, the health of household members, and transportation. Women manage household finances by tightening the fulfillment of household needs, even women have to sacrifice setting aside the fulfillment of their own needs in order to meet the minimum household needs. Women to get out of the poverty trap take advantage of social relations, family ties, and government assistance, even when women have access to look for alternative income, women try to find additional income by working modestly. Keywords : Women; poverty trap; south merapi slope Copyright (c) 2023 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License